Determinan Yang Mempengaruhi Kejadian Hipertensi Di Wilayah Kerja Puskesmas Gunung Alam Kabupaten Bengkulu Utara - Sari, Made Depita; Suyanto, Jipri; Surahman, Fery (CV. Utami, 2025)
Hypertension is one type of non-communicable disease with an incidence rate that continues to increase every year even though promotive and preventive measures have been developed following advances in science and technology. The prevalence of hypertension in Indonesia is 34.1%, an increase compared to the prevalence of hypertension in the 2013 Riskesdas data of 25.8%. Hypertensive disease is the 10th most common disease in the Bengkulu Provincial Health Office and North Bengkulu Regency Office, at Gunung Alam Health Centre hypertension disease increased in 2023 by 210 cases. This study aims to determine the determinants that influence the incidence of hypertension in the Gunung Alam Health Centre Working Area. This type of research is quantitative with a cross sectional design. The sample of this study amounted to 43 people, taken by simple random sampling. Data analysis was carried out with the chi-square test.The results of the analysis showed that most (58.1%) respondents had hypertension, most respondents (53.5%) with a high level of salt consumption, most respondents (62.8%) who experienced mild stress and almost half of the respondents (34.9%) had an insufficient level of health literacy in the Gunung Alam Puskesmas working area, North Bengkulu Regency. Based on bivariate analysis, it was found that there was a significant relationship between salt consumption with p value = 0.000, stress level with p value = 0.000, and health literacy with p value = 0.001 with the incidence of hypertension in the Gunung Alam Health Centre working area, North Bengkulu Regency in 2024. It is expected that hypertensive patients maintain factors associated with the incidence of hypertension and conduct routine examinations at the Gunung Alam Health Centre, North Bengkulu Regency.